A novel implant surface modification mode of Fe3O4-containing TiO2 nanorods with sinusoidal electromagnetic field for osteoblastogenesis and angiogenesis - Ranyue Ren; Jiachao Guo; Hao Song; Yong Wei; Chao Luo; Yayun Zhang; Liangxi Chen; Biao Gao; Jijiang Fu; Wei Xiong (Materials Today Bio, 2023)
Implants made of Ti and its alloys are widely utilized in orthopaedic surgeries. However, insufficient osseointegration of the implants often causes complications such as aseptic loosening. Our previous research discovered that disordered titanium dioxide nanorods (TNrs) had satisfactory antibacterial properties and biocompatibility, but TNrs harmed angiogenic differentiation, which might retarded the osseointegration process of the implants. Magnetic nanomaterials have a certain potential in promoting osseointegration, electromagnetic fields within a specific frequency and intensity range can facilitate angiogenic and osteogenic differentiation. Therefore, this study used Fe3O4 to endow magnetism to TNrs and explored the regulation effects of Ti, TNrs, and Fe3O4-TNrs under 1 ​mT 15 ​Hz sinusoidal electromagnetic field (SEMF) on osteoblastogenesis, osseointegration, angiogenesis, and its mechanism.We discovered that after the addition of SEMF treatment to VR-EPCs cultured on Fe3O4-TNrs, the calcineurin/NFAT signaling pathway was activated, which then reversed the inhibitory effect of Fe3O4-TNrs on angiogenesis. Besides, Fe3O4-TNrs with SEMF enhanced osteogenic differentiation and osseointegration. Therefore, the implant modification mode of Fe3O4-TNrs with the addition of SEMF could more comprehensively promote osseointegration and provided a new idea for the modification of implants.